DETERMINANT FACTORS OF SPATIAL DATA SHARING OF LOCAL SPATIAL DATA INFRASTRUCTURE IN INDONESIA - Asseng, Bau; Rahman, Zulkarnain Abdul; Said, Mohamad Nor (Badan Informasi Geospasial in Partnership with MAPIN, 2018)
This study is based on the phenomenon of the weakness of local government’s response to the national program of Spatial Data Infrastructure for the effective spatial data sharing in Indonesia. This study is investigation of determinant factors of spatial data sharing for local Spatial Data Infrastructure in Indonesia. The purpose of this study is to describe the spatial data-sharing model of Local SDI in Indonesia. It was conducted in West Java Province, Bogor Regency, and Bogor City. Sequential exploratory design method consisting of interview and questionnaire were used in this research. An in-depth interview was used to get a response from 10 participants among IT or GIS staff and head of the department. A total of 75 respondents were involved in questionnaire survey. Content’s analysis was used to measure interview data while Partial Least Square analysis was used to measure questionnaire data. The fit items were chosen after validity and reliability measurement in the structural model analysis using Smart PLS. Hypothesis measurement found that Data sharing practice was significantly affected by the Organization and Technology aspect, but Data sharing practice was less significantly affected by Human Resource and Spatial Data. All R-Square value shows that the value is more than 50% on Technology aspect, Human Resource aspect, Spatial Data aspect, while the R-Square value on Data Sharing practice is 47.3%. Because the Human resource and Spatial data have the less significant effect on spatial data sharing, this research proposed awareness program and mentoring by National government to promote spatial data sharing support at the local SDI.